2013
DOI: 10.1139/apnm-2012-0374
|View full text |Cite
|
Sign up to set email alerts
|

Associations among evening snacking, screen time, weight status, and overall diet quality in young adolescents

Abstract: The purpose of this study was to determine the associations among evening snacking (food choices, portion sizes), afterschool-evening screen time, overall diet quality, and weight status. Participants consisted of 1008 young adolescents (secondary analyses, n = 651) from schools in Windsor-Essex, Ontario. The Web-based Food Behaviour Questionnaire, including a 24-h diet recall, was used to assess eating and screen time behaviours (television and video and computer games), as well as nutrient intake; height and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…A similar interaction between both behaviors, but with mortality as the outcome measure, was found in a large-scale meta-analysis (including over one million men and women), where high levels of moderate intensity physical activity (about 60-75 min per day) eliminated the increased risk of death associated with high sitting time [71]. In addition, previous studies showed that increased screen time was associated with an overall poor diet quality [72,73]. The above indicates possible triangular interactions, again highlighting the importance of combining all energy balance-related behaviors when investigating their association with burn-out risk.…”
Section: Discussionsupporting
confidence: 60%
“…A similar interaction between both behaviors, but with mortality as the outcome measure, was found in a large-scale meta-analysis (including over one million men and women), where high levels of moderate intensity physical activity (about 60-75 min per day) eliminated the increased risk of death associated with high sitting time [71]. In addition, previous studies showed that increased screen time was associated with an overall poor diet quality [72,73]. The above indicates possible triangular interactions, again highlighting the importance of combining all energy balance-related behaviors when investigating their association with burn-out risk.…”
Section: Discussionsupporting
confidence: 60%
“…Adolescent study quality ranged from 4/16 to 15/16, median=8 (scores 19: n=127; 10: n=428–31; 8: n=232 33; 7: n=134; 6: n=518 35–38; 5: n=139; 4: n=140). Study quality scores in adults for studies ranged from 5/16 to 7/16, median=6 (scores 7: n=141; 6: n=118; 5: n=142).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a small number of adolescents identified screen use and studying as a barrier to healthful eating, which has been linked with the consumption of less healthful foods/ beverages in previous studies (42,45) . Participants thought this was related to boredom, lack of awareness, hunger, stress and social reasons, while previous studies have identified distraction, lack of awareness and advertising as factors contributing to overconsumption while watching television (46,47) .…”
Section: Discussionmentioning
confidence: 98%